PROGRAM PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PENGEMBANGAN UMKM OLAHAN CUMI , STUDI DI DESA LANGGULA, KECAMATAN BATUDAA PANTAI, KABUPATEN GORONTALO - Nur Jafar; Funco Tanipu; Sahrain Bumulo (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study aims to explore the impact of a community empowerment program through the development of micro, small, and medium enterprises (MSMEs) based on squid processing in Langgula Village, Batudaa Pantai District, Gorontalo Regency. The research focuses on how the program influences economic welfare, product innovation, production efficiency, and marketing strategies among coastal communities. This study employed a qualitative method with a case study approach, involving seven key informants consisting of village officials, fishermen, and MSME actors. Secondary data were also obtained from literature, statistical reports, and program documentation. Data were collected through in-depth interviews, participatory observation, and document analysis, then processed using data reduction, data display, and conclusion drawing following the Miles and Huberman framework. The results indicate that the empowerment program significantly improved community welfare by providing alternative sources of income, particularly for women involved in MSME activities. Product innovations such as panada cumi (squid-filled pastry), squid chili sauce, ila bulo cumi (grilled squid), and squid dumplings emerged as outcomes of training and mentoring. The use of modern equipment enhanced production efficiency and hygiene, while promotional strategies through social media and local festivals expanded market reach. However, challenges remain in terms of limited capital, restricted market access, and inadequate infrastructure. Overall, the program has transformed community members into active development actors, strengthened household economies, fostered women's group collaboration, and increased women's participation in village development